Novel Nanoparticle-based Colorimetric Probes and Sensors for Determining Phenolic Antioxidants, Biothiols, Nitrite and Hydrogen Peroxide. (2017) - Apak, Reşat; Erçağ, Erol; Özyürek, Mustafa; Güçlü, Kubilay; Üzer, Ayşem; Çelik, Saliha Esin; Bekdeşer, Burcu; Can, Ziya; Sağlam, Şener
Abstract: This study examines the principles and milestones of nanoparticle (NP)-based colorimetric sensors and probes developed by our research group. A novel method for antioxidant capacity estimation was developed on the polyphenol-mediated growth of Ag-NPs and optical monitoring of the corresponding plasmon absorption bands. A new optical sensor using Ellman's reagent-adsorbed gold nanoparticles in colloidal solution was devised to selectively determine biothiols. Nitrite was determined by means of 4-aminothiophenol-modified Au-NPs and naphthylethylene diamine as coupling agent. Hydrogen peroxide was detected with the use of Fe3 O4 magnetite NPs as peroxidase-like catalyst using a N, N -dimethyl- p -phenylenediamine (DMPD) probe.